2017
DOI: 10.1021/acsami.6b11113
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into Pseudo-Capacitance Behavior of Glycoside-Containing Hydrogels

Abstract: Electrochemical pseudocapacitors are an attractive choice for energy storage applications because they offer higher energy densities than electrostatic or electric double layer capacitors. They also offer higher power densities in shorter durations of time, as compared to batteries. Recent efforts on pseudocapacitors include biocompatible hydrogel electrolytes and transition metal electrodes for implantable energy storage applications. Pseudocapacitive behavior in these devices has been attributed to the redox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Amikagel films were generated by cross‐linking between amines in aminoglycoside amikacin with epoxide groups present in PEGDE or BDDE, resulting in gels that contain both amine and hydroxyl groups (Figure S1, Supporting Information). [ 32,45 ] Figure shows various 3D objects that were fabricated following hydration‐triggered actuation and folding of different 2D shapes of AM‐PEGDE films. After placing the film on the surface of water, each shape was seen to curl such that the actuation resulted in minimization of the contact area between the film and the water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amikagel films were generated by cross‐linking between amines in aminoglycoside amikacin with epoxide groups present in PEGDE or BDDE, resulting in gels that contain both amine and hydroxyl groups (Figure S1, Supporting Information). [ 32,45 ] Figure shows various 3D objects that were fabricated following hydration‐triggered actuation and folding of different 2D shapes of AM‐PEGDE films. After placing the film on the surface of water, each shape was seen to curl such that the actuation resulted in minimization of the contact area between the film and the water.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we report hydration‐triggered activation of a single‐component cationic hydrogel, “Amikagel,” [ 31,32 ] derived from an aminoglycoside antibiotic, amikacin (AM), cross‐linked with diglycidyl ethers. The hydrogel is homogeneous in that no gradients of cross‐linking or porosity are intentionally engineered into its morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Biomedical applications are also suggested by the diamond electrode’s ability to operate in physiological solution ( Garrett et al, 2012 ; Falahatdoost et al, 2021 ). This approach has previously been demonstrated with other materials and could be used to power small biomedical devices within the body ( Chae et al, 2017 ; Raravikar et al, 2017 ; Sim et al, 2018 ). It has been suggested that supercapacitors can be used in hybrid devices where batteries or energy harvesting devices provide baseload power and supercapacitors can provide peak power ( Wang et al, 2020b ).…”
Section: Discussionmentioning
confidence: 96%
“…This window can be widened by using ionic liquids, or organic and “water-in-salt” electrolytes (for example [EMIM][BF 4 ], TEABF4/CAN, and LiTFSI, respectively); however, many of these chemicals are flammable or toxic ( Martínez-Casillas et al, 2019 ). Highly toxic electrolytes present a significant health hazard for biomedical applications even if hermetically sealed, and so safer aqueous electrolytes are preferred ( Raravikar et al, 2017 ). Aqueous electrolytes also have high conductivity at room temperature enabling higher P densities, while are generally less expensive than organic electrolytes or ionic liquids ( Simon and Gogotsi, 2013 ; Gao and Nebel, 2016 ; da Silva et al, 2018 ).…”
Section: Supercapacitors and The Allure Of Diamondmentioning
confidence: 99%
See 1 more Smart Citation